Further Experiences in CDIO Implentation - LYONS, CHRISTOPHER; BENNETT, GARETH; KELLY, KEVIN (My University, 2008)
The CDIO (Conceive, Design, Implement and Operate) philosophy has become an increasingly influential engineering educatio n paradigm championed by a range of leading engineering educational institutes worldwide. A previous paper by the authors [1] reported on first experiences in introducing a number of CDIO initiatives in to an engineeri ng undergraduate program. This paper explores the success of these initiatives a year late r, at which stage the influence of the changes can be evaluated through (hopefully incr eased!) student aptitude and interest. Follow-on initiatives in a nu mber of areas are also discussed.
25th International Manufacturing Conference
PUBLISHED
Dublin Institute of Technology
Keywords: Redesign; Systematic Design Techniques; CDIO; Design; Education; Inclusive Society